2000
DOI: 10.1053/jopr.2000.19987
|View full text |Cite
|
Sign up to set email alerts
|

Dentists' preferences of anterior tooth proportion—a Web‐based study

Abstract: Dentists preferred the 80 percent proportion when viewing short or very short teeth and the golden proportion when viewing very tall teeth. Golden proportion was worst for normal height or shorter teeth and the 80% proportion for tall or very tall teeth. They picked no clear-cut best for normal height or tall teeth, and their choices could not be predicted based on gender, specialist training, experience, or patient load.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
131
1
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(146 citation statements)
references
References 7 publications
7
131
1
3
Order By: Relevance
“…The response rate is similar to other web-based surveys (Rosenstiel et al, 2000, Rosenstiel et al, 2004 and the overall number of participants is much larger than any previous survey in this area; however a question does arise concerning the increased risk of nonresponse bias. Groves (Groves, 2006) undertook a review of the literature and found no clear link between response rates and nonresponse bias.…”
Section: Strengths and Weaknessessupporting
confidence: 57%
“…The response rate is similar to other web-based surveys (Rosenstiel et al, 2000, Rosenstiel et al, 2004 and the overall number of participants is much larger than any previous survey in this area; however a question does arise concerning the increased risk of nonresponse bias. Groves (Groves, 2006) undertook a review of the literature and found no clear link between response rates and nonresponse bias.…”
Section: Strengths and Weaknessessupporting
confidence: 57%
“…Several researchers have concluded that golden proportion is more theoretical, artistic and difficult in application in their study on the maxillary anterior widths [20][21][22][23][24][25][26][27][28] Further in aesthetic dentistry, macroesthetic factors play a predominant role rather than factors such as golden proportion which is a microesthetic factor. 29 …”
Section: Discussionmentioning
confidence: 99%
“…14 Approaches involving close-up images, showing only the oral region, have also differed. Images showing only the arrangement of the teeth and gingivae without the surrounding lip curtain have been used [15][16][17] when assessing aspects of smile aesthetics, but in doing so, may alter the opinion of the assessor. This can be overcome by using images of the teeth and gingivae surrounded by the lips, thereby presenting an image that will let the assessor more easily assess the overall smile aesthetic.…”
Section: Discussionmentioning
confidence: 99%